Tracking the Cheshire Cat: Ethnic Americans and American Ethnicity on Cape Breton Island - Taft, Michael (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1991)
Among the largest, yet most neglected, ethnic groups in Canada are those who have emigrated from the United States. While their differences from other ethnie and immigrant groups are quite evident — no American clubs, festivals, native foods and dances, etc. — their identity as a national, immigrant group with certain shared ethnie traits is undeniable. The problem remains, however: how can this group be characterized according to its shared ethnicity? The answer is not easy. Using material gathered from interviews with ethnie Americans now living on Cape Breton Island, this paper explores the question of Americanness, group identity, the context of the group, and ethnicity itself.